1976
DOI: 10.2337/diab.25.7.554
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy in Pima Indians: Relationships to Glucose Level, Duration of Diabetes, Age at Diagnosis of Diabetes, and Age at Examination in a Population with a High Prevalence of Diabetes Mellitus

Abstract: The occurrence of retinopathy and its relationship to diabetes in 1,640 Pima Indians age 15 and over has been determined. Eighteen per cent of those with two-hour postload plasma glucose levels of equal to or greater than 200 mg./dl. had some evidence of retinopathy. Of those with retinopathy and diabetes, 7 per cent were found to have proliferative or neovascular changes, the remainder having microaneurysms and/or exudates. The frequency of retinopathy increased from 3 per cent among newly diagnosed diabetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…However, the subsequent This, together with differences in the definition of retinopathy, could contribute to inconsistent results in the literature. Dorf et al (19) studied 1,640 Pima Indians and found the prevalence of retinopathy to increase from 3% at presentation to 47% in those with diabetes for >10 years. After adjusting for duration, there was no effect of age at diagnosis on the prevalence of retinopathy.…”
Section: Retinopathymentioning
confidence: 96%
“…However, the subsequent This, together with differences in the definition of retinopathy, could contribute to inconsistent results in the literature. Dorf et al (19) studied 1,640 Pima Indians and found the prevalence of retinopathy to increase from 3% at presentation to 47% in those with diabetes for >10 years. After adjusting for duration, there was no effect of age at diagnosis on the prevalence of retinopathy.…”
Section: Retinopathymentioning
confidence: 96%
“…In previous studies, the prevalence and risk factors for diabetic retinopathy in the Pima Indians with type 2 diabetes were generally similar to those reported in other populations. Diabetic retinopathy in Pima Indians is associated with measures of glycemia and duration of diabetes (13)(14)(15).…”
mentioning
confidence: 99%
“…In the present study, the incidence and progression of diabetic retinopathy were examined to learn whether Hispanics had excess risk compared with NHWs with type 2 diabetes living in the San Luis Valley of Colorado. Because glucose control, hypertension, type of therapy, and diabetes duration, among other risk factors, are associated with diabetic retinopathy (1,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), we also examined these and other factors to see if they accounted for altered Hispanic-to-NHW incidence rates.…”
mentioning
confidence: 99%